Silver/silver halide supported on mesoporous ceria particles and photo-CWPO degradation under visible light for organic compounds in acrylonitrile wastewater. Issue 43 (5th August 2021) - Zhao, Guozheng; Tan, Qingwei; Li, Changbo; Shang, Liyan; Zhang, Daihang; Lu, Xuanxuan; Qiu, Feng
Abstract : Silver/silver halide supported on ordered mesoporous ceria particles (Ag/AgCl/CeO2 ) were prepared by microwave-assisted soft template method, deposition precipitation method and photoreduction method, and its catalytic performance was investigated. Abstract : Silver/silver halide supported on ordered mesoporous ceria particles (Ag/AgCl/CeO2 ) were rapidly prepared by microwave-assisted soft template method, deposition precipitation method and photoreduction method, using cerium nitrate and silver nitrate as raw materials and block copolymer F127 as a template. The morphology, structure and chemical composition of the catalyst were characterized by XRD, SEM, EDS, TEM, N2 adsorption–desorption and UV-Vis Drs. Catalytic wet peroxide system assisted with visible light photocatalysis (photo-CWPO) was conducted to investigate the performance of organics degradation by Ag/AgCl/CeO2 as a catalyst in acrylonitrile wastewater. The results showed that the Ag/AgCl/CeO2 prepared has an ordered mesoporous structure, Ag and AgCl are formed on the surface of CeO2, with a specific surface area of 302.6–336.2 m 2 g −1 and the average pore size is 8.04–8.90 nm. There is a strong absorption in the visible region and a band gap of 2.9 eV. The Ag/AgCl/CeO2 catalyst has higher catalytic performance in the photo-CWPO system than in the CWPO system alone. Ag loading, catalyst and H2 O2 dosage, and pH value can affect the COD removal. When the concentration of COD in acrylonitrile wastewater was 500 mg L −1, the amount of catalyst was 200 mg, the amount of H2 O2 (30%) was 8 mL, and the reaction time was 60 min, the COD removal reached 90%.